Using mobile disaster response system in bridge management - Tsai, Ming-Kuan; Yau, Nie-Jia (Journal of Civil Engineering and Management, 2014)
Over the years, various hydro-meteorological disasters have impacted many countries and civilians, thus decreasing the losses caused by these disasters has become important for disaster management. While bridges often are essential to connect the affected disaster areas, this study focuses on bridge management associated with typhoons and rain-storms. Recently, although numerous information technology-based applications are available, three problems (i.e. asynchronous information records, unsteady information transmission, and inaccessible information analysis) still influence responses on disaster sites. Therefore, this study integrated several mobile information techniques to propose a mobile disaster response system. The applied mobile GPS- and GIS-based data reports simplify information generation, AR-based assistance enhances information representation, and mobile 3D graphics accelerates information processes. Based on the tests, this system not only improved the recognized problems but also strengthened the cooperation between construction engineers and workers and disaster managers. Overall, this study is a useful reference for similar applications in bridge management and disaster management.